MULTIMODAL READING TEXTS AND EFL UNDERGRADUATES’ ACADEMIC WRITING DEVELOPMENT: A QUALITATIVE CASE STUDY IN INDONESIA - Atalisi Zalukhu; Fitria Rahmawati; Yuanita Arianti; Aliya Noor Cahyani (Universitas HKBP Nommensen, 2026)
The integration of reading and writing has long been recognized as a crucial component in second language learning. However, most previous studies have focused primarily on linear academic texts, with limited attention to the role of multimodal reading materials in supporting students’ academic writing development. This study investigates how multimodal reading texts influence the academic writing development of English as a Foreign Language (EFL) students. Using a qualitative case study design, the study involved approximately 20–25 undergraduate students enrolled in an Academic Writing course in an English Language Education program. Data were collected through classroom observations, analysis of students’ writing samples, and semi-structured interviews. The data were analyzed using thematic analysis and qualitative discourse analysis to examine patterns in students’ perceptions and developments in their written texts. The findings reveal that exposure to multimodal texts such as infographics, visual essays, and digitally enriched articles enhances students’ ability to generate ideas, organize arguments, expand lexical choices, and engage critically in academic writing. Students also demonstrate an improved capacity to synthesize information from multiple modes into coherent written arguments. These results suggest that integrating multimodal reading materials into writing instruction can effectively support academic writing development in EFL contexts. However, the findings are limited to a single instructional setting and a relatively small participant group; therefore, caution should be exercised in generalizing the results. Nevertheless, the study provides transferable pedagogical insights for integrating multimodal reading and writing practices in higher education EFL classrooms.